The Impact of Lisbon Criteria on Business Development in Lithuania - Garuckas, Rimantas; Serafinas, Dalius (Ekonomika, 2005)
The aim of the paper is to review the Lisbon criteria that are influencing business in Lithuania, and to outline the main perspectives of national businesses in the EU context. To this end, we have analyzed earlier works on the factors and parameters that influence business environment in the EU, compiled a list of most crucial factors influencing the business entities, interviewed the top management of 300 top Lithuanian companies in order to find out the peculiarities of the Lithuanian way to success in business. Managers’ opinions were compared to facts stated in internal documents (especially documents containing market requirements) as to quality and price; internal costs and efficiency of processes. The following methods of research were employed: metaanalysis, documentation review, triangulation, interviews, basic methods of mathematical statistics.